Outline of microbial fuel cells technology and their significant developments, challenges, and prospects of oxygen reduction electrocatalysts - Elangovan, Kavery; Saravanan, Prabhu; Campos, Cristian H.; Sanhueza-Gómez, Felipe; Khan, Md. Maksudur Rahman; Chin, Sim Yee; Krishnan, Santhana; Viswanathan Mangalaraja, Ramalinga (Frontiers in Chemical Engineering, 2023)
The microbial fuel cells (MFCs) which demonstrates simultaneous production of electricity and wastewater treatment have been considered as one of the potential and greener energy production technology among the available bioelectrochemical systems. The air-cathode MFCs have gained additional benefits due to using air and avoiding any chemical substances as catholyte in the cathode chamber. The sluggish oxygen reduction reaction (ORR) kinetics at the cathode is one of the main obstacles to achieve high MFC performances. Platinum (Pt) is one of the most widely used efficient ORR electrocatalysts due to its high efficient and more stable in acidic media. Because of the high cost and easily poisoned nature of Pt, several attempts, such as a combination of Pt with other materials, and using non-precious metals and non-metals based electrocatalysts has been demonstrated. However, the efficient practical application of the MFC technology is not yet achieved mainly due to the slow ORR. Therefore, the review which draws attention to develop and choosing the suitable cathode materials should be urgent for the practical applications of the MFCs. In this review article, we present an overview of the present MFC technology, then some significant advancements of ORR electrocatalysts such as precious metals-based catalysts (very briefly), non-precious metals-based, non-metals and carbon-based, and biocatalysts with some significant remarks on the corresponding results for the MFC applications. Lastly, we also discussed the challenges and prospects of ORR electrocatalysts for the practical application of MFCs.